Giant Osmotic Energy Conversion through Vertical-Aligned Ion-Permselective Nanochannels in Covalent Organic Framework Membranes - Cao, Li; Chen, I-Chun; Chen, Cailing; Shinde, Digambar B.; Liu, Xiaowei; Li, Zhen; Zhou, Zongyao; Zhang, Yuting; Han, Yu; Lai, Zhiping (Journal of the American Chemical Society, 2022)
Nanofluidic membranes have been demonstrated as promising candidates for osmotic energy harvesting. However, it remains a long-standing challenge to fabricate high-efficiency ion-permselective membranes with well-defined channel architectures. Here, we demonstrate high-performance osmotic energy conversion membranes based on oriented two-dimensional covalent organic frameworks (COFs) with ultrashort vertically aligned nanofluidic channels that enabled efficient and selective ion transport. Experiments combined with molecular dynamics simulations revealed that exquisite control over channel orientation, charge polarity, and charge density contributed to high ion selectivity and permeability. When applied to osmotic energy conversion, a pair of 100 nm thick oppositely charged COF membranes achieved an ultrahigh output power density of 43.2 W m–2 at a 50-fold salinity gradient and up to 228.9 W m–2 for the Dead Sea and river water system. The achieved power density outperforms the state-of-the-art nanofluidic membranes, suggesting the great potential of oriented COF membranes in the fields of advanced membrane technology and energy conversion.